Online Candidate Selection System for Elections - Meregngnage H.E.; Fernando J.A.T.C.; Fernando W.K.; Fernando N.M.R.M. (International Journal of Engineering and Management Research, 2023)
This research proposes an innovative online platform for political parties in Sri Lanka to enhance the candidate selection process. The platform incorporates features such as sentiment analysis, background checks, aptitude tests, ranking system, and analysis of candidates' promises and activities. Developed using advanced technologies, it aims to ensure transparency, efficiency, and accessibility for all eligible candidates, ultimately contributing to a more democratic election.